IMPROVING ACHIEVEMENT OF LEARNING MATH EXERCISE TRAINING BASED ON SETTING PROJECTS COOPERATIVE TYPE STAD IN CLASS X-4 STUDENTS SMA NEGERI 6 MAKASSAR - Natsir M, M (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2015)
This study was classroom action research conducted in two  cycles with the topic of Quadratic Equations. The subject of this study were all students of class X-4 SMAN 6 Makassar, South Sulawesi Province academic year 2009/2010 second semester, as many as 40 students, consisting of 10 males and 30 females. This research aimed to improve mathematics achievement through the project-based practice with cooperative setting STAD type. Indicators, used in terms of process were ; (1) the improvement of students activities in the process of giving project-based practices with cooperative setting STAD type, (2) the increase of teachers’ ability to manage the learning of mathematics through project-based practices with cooperative setting STAD type, and in terms of outcomes are ; (1) the increased of mathematics achievement through project-based practices with cooperative setting STAD type, (2) students’ responses toward the learning activities more than 50% students responded positively to at least 70% of the amount aspects, questioned in mathematics learning through project-based practices with cooperative setting STAD type. The results showeds that through project-based practices with cooperative setting STAD type can improve mathematics achievement, as indicated by ; (1) through project-based practices with cooperative setting STAD type can increase students activity in learning mathematics, from the average ideal criteria of 19,6 from the ideal score 100 in cycle I  becomes 21,45 from the ideal score 100 in cycle II, (2) through project-based practises with cooperative setting STAD type can increase the ability to manage mathematics learning from high category with an average of 3,8 from the ideal score of 4,5 in cycle I becomes 3,9 from the ideal score 4,5 in cycle II, (3) through project-based practices with cooperative setting STAD type can improve students achievement as a result of learning mathematics from the average grade 65,90 from the ideal score of 100 with the completeness percentage of 57,5% in the beginning score becomes 71,73 from the ideal score 100 with the completeness percentage of 80,0% in cycle I and in cycle I becomes 77,25 from the ideal score 100 with percentage of 95,5%, and the standard deviation in the initial score 7,98 the score in cycle I 9,36, the score in cycle II 8,65, and (4) through project-based practices with cooperative setting STAD type can give positive respond toward mathematics learning in quadratic equations as many as 76,75% from 6 items and 20 aspects that are responded